The Microbiome-Gut-Brain Axis in Multiple Sclerosis - Radojević, Dušan; Soković Bajić, Svetlana; Dinić, Miroslav; Bisenić, Aleksandar; Djokić, Jelena; Golić, Nataša (Archives of Pharmacy, 2023)
The microbiome-gut-brain axis (MGBA) represents a close two-way relationship between the gut and the central nervous system (CNS) mediated by the immune system, the enteric nervous system (ENS), the vagus nerve, and the gut microbiome. Gut microbes, including bacteria, fungi, and viruses, can communicate with the CNS and modulate the physiology of the brain in health and disease, which marks them as an important MGBA factor. It is becoming increasingly evident that gut microbiome dysbiosis is implicated in the onset and severity of different neurodegenerative and psychiatric diseases including multiple sclerosis (MS). MS is a chronic disease of the CNS associated with different genetic and environmental risk factors. Neuroinflammation and demyelination in the brain and the spinal cord are hallmark features of MS. The accumulating evidence shows that the MGBA, although a relatively new concept, has an important role in MS. Therefore, the purpose of this article is to review recent research on the gut-brain connection in MS, and to highlight MS-associated gut microbiota constituents and the role of bacterial metabolites in MS.